2015
DOI: 10.1016/j.bbi.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 4 and comorbid pain in Interstitial Cystitis/Bladder Pain Syndrome: A Multidisciplinary Approach to the Study of Chronic Pelvic Pain research network study

Abstract: Background Interstitial Cystitis/Bladder Pain Syndrome (IC/BPS) is a condition characterized by pelvic pain and urinary symptoms. Some IC/BPS patients have pain confined to the pelvic region, while others suffer widespread pain. Inflammatory processes have previously been linked to pelvic pain in IC/BPS, but their association with widespread pain in IC/BPS has not been characterized. Methods Sixty-six women meeting criteria for IC/BPS completed self-report measures of pain as part of the Multidisciplinary Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 52 publications
(65 reference statements)
2
51
0
Order By: Relevance
“…The URO‐OVA model presents altered TLR4 activation, 124 which is consistent with our recent findings suggesting a significant role of TLR4 in IC/BPS pain 125 . To determine the role of TLR4, we generated URO‐OVA TLR4−/− mice that retained the urothelial OVA expression, but lacked TLR4 expression 124 .…”
Section: Animal Modelssupporting
confidence: 85%
“…The URO‐OVA model presents altered TLR4 activation, 124 which is consistent with our recent findings suggesting a significant role of TLR4 in IC/BPS pain 125 . To determine the role of TLR4, we generated URO‐OVA TLR4−/− mice that retained the urothelial OVA expression, but lacked TLR4 expression 124 .…”
Section: Animal Modelssupporting
confidence: 85%
“…We have recently identified Toll-Like Receptor (TLR) inflammatory responses in peripheral blood mononuclear cells (PBMCs) and diurnal cortisol dysregulation as robust correlates of the IC/BPS syndrome. 6,7 Specifically, we found that the TLR-2 inflammatory response and diurnal cortisol dysregulation, marked by a flattened diurnal cortisol rhythm, served as possible biomarkers of IC/BPS while TLR-4 inflammatory responses were associated with greater IC/BPS pain severity 6 and the extent of comorbid pain. 7 …”
Section: Introductionmentioning
confidence: 80%
“…Participants were 24 women participating in a larger volunteer cohort study (n=66) previously reported on 6,7 who agreed to complete a longitudinal study of symptom changes. Demographic and symptom information was collected during a baseline visit, after which symptom data was collected bi-weekly for 48 weeks via an online module (25 time-points, including baseline).…”
Section: Methodsmentioning
confidence: 99%
“…Hyperalgesia is typically assessed by identifying pain thresholds in individuals using standardized stimuli facilitated by pressure devices such as algometers, ischemic cuff algometry, or computerized mechanical testing devices such as the Multimodal Automated Sensory Testing (MAST) System (AMI, Ann Arbor, MI https://www. arbormedicalinnovations.com/) (Harte et al, 2013(Harte et al, , 2016Henry et al, 2014;Schrepf et al, 2015;Wasserman et al, 2015)-an automated QST platform. In patients presenting with a localized pain complaint, increased pain sensitivity at remote or unaffected body areas is strongly suggestive of central pain mechanisms and is a common feature of the COPCs (Berkley, Cason, Jacobs, Bradshaw, & Wood, 2001;Chaves et al, 2016;Janig, 2015;Jayaram et al, 2015;McAllister, McGinty, Resuehr, & Berkley, 2009;Scheich et al, 2017;Toriyama, Horiuchi, & Hongo, 2017).…”
Section: Generalized Sensory Hypersensitivitymentioning
confidence: 99%